Shared Instructional Leadership of School Administrators: Its Relationship to Teachers’ Self-Efficacy - Romero, Marcian Xavier (The Indonesian Institute of Science and Technology Research, 2024)
The study determined the relationship between shared instructional leadership among school administrators and teachers' self-efficacy. The study employed a concurrent parallel mixed method using a descriptive-evaluative-correlational research design. The descriptive design was used to ascertain the level of shared instructional leadership of school administrators and teachers and the level of self-efficacy of teachers. The evaluative design was employed to underscore the significant differences between shared instructional leadership and self-efficacy among groups of respondents. Meanwhile, the correlational design assessed the critical relationship between shared instructional leadership and teachers' self-efficacy. Data revealed that administrators and teachers have a very high level of shared instructional leadership and self-efficacy, which was derived based on the survey's descriptive results. There was a significant difference among groups of respondents and no statistically significant difference among shared instructional leadership and self-efficacy. The alternative hypothesis that no meaningful relationship exists between shared instructional leadership and teacher self-efficacy was also accepted.